1990
DOI: 10.1111/j.1365-2672.1990.tb02921.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of Bdellovibrio spp. in man‐made water systems: coexistence with legionellas

Abstract: Bdellovibrios have been isolated from surface waters but there are no reports of its occurrence in mains water supplies. One hundred and thirty five water samples from 81 sources were examined for the presence of Bdellovibrio bacteriovorus and Legionella spp. Bdellovibrios were isolated by a double-layer agar technique with two strains of Legionella pneumophila serogroup 1 as the host organisms. Bdellovibrio spp. were isolated from 57.8% and Legionella spp. from 9.5% of the samples. The two species occurred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…After their initial discovery, Bdellovibrios were isolated from various habitats and found to be widely distributed in aquatic and terrestrial environments (6)(7)(8)(9). Since its discovery and up to the time of writing this review, more than 390 articles have been published concerning this bacterium and similar organisms.…”
Section: Historical Perspective the Early Years (1962-1992)mentioning
confidence: 99%
“…After their initial discovery, Bdellovibrios were isolated from various habitats and found to be widely distributed in aquatic and terrestrial environments (6)(7)(8)(9). Since its discovery and up to the time of writing this review, more than 390 articles have been published concerning this bacterium and similar organisms.…”
Section: Historical Perspective the Early Years (1962-1992)mentioning
confidence: 99%
“…This lifestyle bears some similarities to that of bacteriophages, which "nd their host by di!usion, inject their genetic material, proliferate within the cell and emerge after cell lysis. Bdellovibrios occur in a wide range of habitats, ranging from lowdensity, aquatic, ecosystems (Richardson, 1990;Schoe$eld & Williams, 1990;Rice et al, 1998), to high-density ecosystems such as rhyzosphere soil communities (Elsherif & Grossmann, 1996) and the gut #ora of some vertebrates (Imbragimov, 1980). There are indications that they may associate with surface bio"lms in aquatic environments (Kelley et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…soil, marine sediments, rhizosphere of plants, sewage, etc. (1)(2)(3)(4). In the latter environment it was found that Bdellovibrionaceae are involved in the reduction of bacterial counts thus supporting the self-purification of domestic waste waters (4,5).…”
mentioning
confidence: 95%
“…(1)(2)(3)(4). In the latter environment it was found that Bdellovibrionaceae are involved in the reduction of bacterial counts thus supporting the self-purification of domestic waste waters (4,5). Furthermore, Bdellovibrionaceae were found in the intestinal tract of mammals and might be important for the reduction of pathogenic bacteria in this environment (6,7).…”
mentioning
confidence: 95%